An overview of the Castelporziano experiments - Seufert, G; Bartzis, J; Bomboi, T; Ciccioli, P; Cieslik, S; Dlugi, R; Foster, P; Hewitt, C N; Kesselmeier, J; Kotzias, D; Lenz, R; Manes, F; et al. (Atmospheric Environment, 1997)
This paper reviews the major outcomes of the measuring campaigns performed at the Castelporziano nature preserve near Rome, Italy, by 14 European laboratories as part of the BEMA (Biogenic Emissions in the Mediterranean Area)-project. Six campaigns of 1–4 weeks duration were carried out in different seasons of the years 1993–1994 at semi-continuously running test plots in the nature reserve, representing common Mediterranean vegetation types. The aim was to characterise, at the different test plots, the atmospheric chemical and meteorological situations, the plant biomass and physiology, the type, amount and controls of emissions from different plants by means of branch enclosures, and the BVOC emission fluxes from different ecosystems, by scaling up enclosure data from individual sources, and by measuring fluxes directly by use of micrometeorological methods. An important focus during the initial phase of the five year BEMA-project was the harmonisation and improvement of the analytical, physiological and micrometeorological methods used, and the development and testing of new methods for measuring BVOC fluxes.
Keywords: air chemistry; Biogenic emission; ecophysiology; Mediterranean area; micrometeorology; Vegetation